Image-Guided Chondrocyte Harvesting for Autologous Chondrocyte Implantation: Initial Feasibility Study with Human Cadaver and Pilot Clinical Experience. Issue 2 (April 2019) - Zikria, Bashir; Hafezi-Nejad, Nima; Patten, Ian; Johnson, Alex; Haj-Mirzaian, Arya; Wilckens, John H.; Ficke, James R.; Demehri, Shadpour
Abstract : Background: Autologous chondrocyte implantation (ACI), a promising modality for repairing full-thickness cartilage defects, requires 2 consecutive arthroscopic procedures for chondrocyte harvesting and implantation. In the present study, we assessed the feasibility and efficacy of image-guided chondrocyte harvesting as an alternative to arthroscopic biopsy. Methods: We induced full-thickness cartilage defects in 10 human cadaveric knees. Computed tomographic arthrography (CTA) was performed following the intra-articular administration of Omnipaque 350 to measure the diameters of the induced cartilage defects. Subsequently, 2 independent operators conducted CTA-guided chondrocyte harvesting (from the medial and lateral trochlear ridges) in each knee. The time for chondrocyte harvesting, accuracy (distance between the predefined target on CTA and the final insertion site of the needle), and number of needle readjustments were recorded. In the institutional review board-approved clinical study, informed consent was obtained and chondrocyte harvesting was performed both with use of a conventional arthroscopic biopsy method and with use of a needle through an arthroscopy access site in 10 subjects for whom ACI was indicated. The samples were processed and cultured blindly, and the quantity and quality of the samples were determined. Results: CTA measurements of full-thickness cartilage defects showed high to perfect absolute agreement and consistency when compared with direct measurements (overall interclass correlation coefficient, 0.933 to 0.983; p < 0.05). For both operators, image-guided chondrocyte harvesting from the lateral ridge was more accurate (p = 0.007 and 0.040) and faster (p = 0.056 and 0.014) in comparison with harvesting from the medial ridge. In the clinical study, no significant difference was observed for the growth index of samples between the needle-harvest and conventional methods (p = 0.897). Conclusions: CTA can be used for precise measurement of full-thickness cartilage defects. Image-guided chondrocyte harvesting is a viable alternative to traditional arthroscopic biopsy for ACI. Clinical Relevance: We recognize the current pivotal role of arthroscopic biopsy, as a part of ACI, for chondrocyte harvesting as well as for delineating the nature of the lesion. However, on the basis of our results, image-guided chondrocyte retrieval may obviate the need for arthroscopic biopsy in some patients in the future.